The Impact of Educational Platforms on Self- learning from the Point of View of Jordanian University Students - Toumeh, Mysoon Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aimed to determine the impact of educational platforms on self- learning from the point of view of Jordanian university students, and to find out whether there are statistically significant differences in the responses of the study sample due to the variables (gender, school year, and family income). The researcher used the descriptive approach, and prepared a questionnaire consisting of (19) items, divided into two fields. The study sample consisted of (235) male and female students, they were chosen by the accessible method, and the results showed a very large impact of educational platforms on self- learning, with an arithmetic mean (4.29), and a percentage (85.8%). 4.22), a percentage (84.4%), and the results of the study did not show any statistically significant differences in the impact of educational platforms on self- learning due to the study variable (gender, school year, and family income). The study recommended the need to take advantage of the positive impact of using educational platforms in developing and enhancing the self- learning skills of Jordanian university students.
Keywords: educational platforms; self- learning